2018
DOI: 10.1186/s12884-018-2079-4
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes following nonobstetric surgery during gestation: a nationwide population-based case-control study in Taiwan

Abstract: BackgroundWhether nonobstetric surgery during gestation is associated with a higher risk of spontaneous abortion or adverse delivery outcomes is still unclear.MethodsWe performed a retrospective case-control study using a Longitudinal Health Insurance Database (LHID 2000) containing claim-data of 1 million randomly selected beneficiaries. We compared the incidences and estimated the adjusted odds ratios (aOR) with 95% confidence interval (95% CI) for spontaneous abortion, adverse delivery outcomes, cesarean de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 25 publications
(40 reference statements)
4
47
0
Order By: Relevance
“…Ibiebele et al showed an equal risk of SGA in laparoscopy and laparotomy, confirming that it is acceptable to combine these procedures when studying the risk of SGA. As in most other studies, we found an increased risk of miscarriage following surgical procedures during pregnancy. Direct comparison of magnitudes of the risk of miscarriage between studies is difficult because of variations in definition of exposure, varying time from exposure and varying completeness of miscarriages.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Ibiebele et al showed an equal risk of SGA in laparoscopy and laparotomy, confirming that it is acceptable to combine these procedures when studying the risk of SGA. As in most other studies, we found an increased risk of miscarriage following surgical procedures during pregnancy. Direct comparison of magnitudes of the risk of miscarriage between studies is difficult because of variations in definition of exposure, varying time from exposure and varying completeness of miscarriages.…”
Section: Discussionsupporting
confidence: 89%
“…As in most other studies, 12,13,16,17 we found an increased risk of miscarriage following surgical procedures during pregnancy. Our results should be interpreted while considering some limitations.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations